(untitled) (Revista Torreón Universitario, 2022)
This study aims to analyze the relation between the credit granted by the national financial system and economic growth measured by the Gross Domestic Product (GDP) in Nicaragua in the period 2011 to 2021. In the last decade, the gross credit portfolio has represented on average 32.11% of Nicaragua’s GDP and in 2017 this same relation represented 40%, which allows us to infer that economic growth depends on the levels of credit that are granted within the economy. To determine the degree of relation that exists between the variables, Pearson’s correlation model was used to know the relation that exists between both variables, which in this case would be the Gross Domestic Product seen from the perspective of production and the gross credit portfolio of the financial system, taking into account that there is a linear relation between the variables. As a result, it was obtained that there is a highly significant degree of relationship between both variables, which indicates that to the extent that the credit portfolio grows in the same way as GDP does, significantly depending on the economic growth of the levels of credits granted within the economy, this growth is susceptible to exogenous events which modify the course of economic growth.